2017
DOI: 10.1515/jolace-2017-0002
|View full text |Cite
|
Sign up to set email alerts
|

English language pre-service and in-service teachers’ self-efficacy and attitudes towards integration of students with learning difficulties

Abstract: The study of foreign languages is obligatory for all pupils in Slovakia, where the first foreign language is English. Conforming to integration legislation, pupils with special educational needs (SEN) are taught in mainstream classes. Foreign language teachers, however, lack training and where not prepared how to apply teaching methods and techniques for pupils with SEN in the regular language learning class. In the study presented, 187 elementary school teachers filled out questionnaires dealing with integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…e study of neurons and artificial neural networks in the human brain may produce a new generation of artificial intelligence machines, that is, neural computers [20]. Now, neural networks are widely used in pattern recognition, image processing, combination optimization, automatic control, information processing, robotics, artificial intelligence, and other fields [21,22]. e convolution operation of the convolution layer is divided into continuous convolution and discrete convolution.…”
Section: 1mentioning
confidence: 99%
“…e study of neurons and artificial neural networks in the human brain may produce a new generation of artificial intelligence machines, that is, neural computers [20]. Now, neural networks are widely used in pattern recognition, image processing, combination optimization, automatic control, information processing, robotics, artificial intelligence, and other fields [21,22]. e convolution operation of the convolution layer is divided into continuous convolution and discrete convolution.…”
Section: 1mentioning
confidence: 99%
“…Актуалізовані документи [2; 4; 14; 15], державні освітні стандарти вимагають, щоб учні із ООП вивчали англійську мову, активно нею послуговувалися, використовували в процесі навчання, подальшому самостійному житті. Доцільними видаються поради словацької дослідниці І. Цімерманової [13], яка зокрема, рекомендує таке: "варто демонструвати максимальну колаборацію; брати до уваги індивідуальний темп та режим роботи учня; використовувати мультисенсорний підхід, поєднувати візуалізацію та вербалізацію; чергувати комунікацію із фізичними вправами; обовʼязково закріплювати нові граматичні структури в усних мовленнєвих вправах; нову лексику тренувати у фразах; віддавати перевагу усному мовленню; використовувати той самий шрифт і тип літер; текст повинен розміщуватись лінійно, а не у вигляді колонок; не рекомендується практикувати дослівний переклад; застосовувати глобальний метод у навчанні читання; використовувати аудіозаписи для тренування правильної вимови" [13] (більш докладно про це в нашій окремій публікації [10]).…”
Section: Foreign Language Education In the Context Of The Principles ...unclassified
“…It can favor the student by helping him to generate a greater reflective capacity, corresponding to a positive effect on the intellectual type. Cimermanová (2017) reported that teachers should improve their attitudes toward inclusive education. Schools create and provide educational programs that specialize according to the type of disability.…”
Section: Teaching Strategies For Improving Inclusive Educationmentioning
confidence: 99%